Risky sexual behaviour among Russian adolescents: association with internalizing and externalizing symptoms - Johan Isaksson; Caroline Westermark; Roman A. Koposov; Andrew Stickley; Vladislav Ruchkin (BMC, 2021)
Abstract Background Risky sexual behaviour (RSB) is regarded as a major health problem during adolescence. Russia has one of the highest rates of teenage pregnancy, abortion and newly diagnosed HIV infections in the world, but research on RSB in Russian youth has been limited. To address this deficit, this study examined the role of several factors, including internalizing and externalizing symptoms, in RSB among Russian adolescents. Methods Self-reported data were collected from 2573 Russian adolescents aged 13-17 years old (59.4 % girls; Mean age = 14.89) regarding RSB (unprotected sex, early pregnancy, multiple sexual partners and substance use during sexual encounters). Information was also obtained on externalizing (conduct problems and delinquent behaviour) and internalizing (depression, anxiety and posttraumatic stress) symptoms, as well as interpersonal risk and protective factors (affiliation with delinquent peers, parental involvement and teacher support). Hierarchical multiple binary logistic regression analysis was used to examine the associations between these variables and RSB. Results Boys reported engaging in more RSB than girls. Externalizing symptoms and affiliation with delinquent peers were most strongly associated with RSB, whereas symptoms of anxiety were negatively associated with RSB. There was an interaction effect for sex and affiliation with delinquent peers on RSB with boys reporting RSB when having more delinquent peers. Neither parental involvement nor teacher support were protective against RSB. Conclusions Early detection of and interventions for RSB and associated externalizing symptoms may be important for adolescent physical and mental wellbeing. Affiliation with delinquent peers should, especially among boys, be regarded as a risk marker for RSB.